Types of Borderline Personality Disorder (BPD) in patients admitted for suicide-related behavior - Rebok, Federico (2015)
Borderline personality disorder (BPD) is determined by the presence of any five of nine diagnostic criteria, leading patients with heterogeneous clinical features to be diagnosed under the same label without an individualized clinical and therapeutic approach. In response to this problem, Oldham proposed five types of BPD: affective, impulsive, aggressive, dependent and empty. The present study categorized a sample of BPD patients hospitalized due to suicide-related behavior according to Oldham’s BPD proposed subtypes, and evaluated their clinical and demographic characteristics. Data were obtained from a sample of 93 female patients admitted to the « Dr. Braulio A. Moyano » Neuropsychiatric Hospital following suicide-related behavior. A total of 87 patients were classified as affective (26 %), impulsive (37 %), aggressive (4 %), dependent (29 %), and empty (5 %). Patients classified as dependent were significantly older at the time of first suicide-related behavior (p = 0.0008) and reported significantly less events of previous suicide-related behaviors (p = 0.03), while patients classified as impulsive reported significantly higher rates of drug use (p = 0.02). Dependent, impulsive and affective BPD types were observed most frequently in our sample. Findings are discussed specific to demographic and clinical implications of BPD patients reporting concurrent suicidal behavior.